Synthesis of Homotaurine and 1-Substituted Homotaurines from α,β-Unsaturated Nitriles - Ma, Yunhai; Xu, Jiaxi (Synthesis, 2012)
Homotaurine and a series of 1-substituted homotaurines were readily synthesized in satisfactory to good yields via the Michael addition of thioacetic acid to aliphatic and aromatic α,β-unsaturated nitriles followed by lithium aluminum hydride mediated reduction and performic acid oxidation. The synthesis of 1,1-disubstituted homotaurines was attempted with β,β-disubstituted acrylonitriles as starting materials but failed due to steric hindrance. The current process is an efficient method for the synthesis of 1-substituted homotaurines.
Keywords: acrylonitrile; amino thiols; Michael addition; nucleophile; reduction; oxidation; thioacetic acid